Pengaruh Dinding Penghalang pada Deteksi Tanda Vital Pernapasan dengan Through Wall Radar - Fildha Ridhia; Aloysius Adya Pramudita; Yuyu Wahyu; Harfan Hian Ryanu (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
Through-Wall Radar (TWR) has been extensively applied in various fields, one of which is in the search for, or evacuation of disaster victims struck by rubbles. The TWR is an application of radar systems operating in a wide frequency range or ultra-wideband (UWB), hence it has a high accuracy level in detecting objects behind walls. In this study, the Vivaldi antenna was used to obtain a high-level resolution for its capability to operate on UWB. Parameters such as dielectric characteristics are needed for each barrier type to generate a high accuracy level. The experiment was conducted to determine the effect of barrier walls on the detection of vital signs of respiration using a radar system modeled using two methods, namely, a vector network analyzer (VNA) and bladeRF. The experiment stages included the making of the experimental system design, experimental data collection, experimental data processing, and experimental results analysis. Wall types used in this study were brick and wooden walls. The experimental data results were used to analyze the effect of the barrier on the detection of vital signs of respiration using a radar system. Experiments using VNA as a radar system were conducted to analyze the effect of the barrier wall on the detection of the target behind the barrier wall. Experiments using bladeRF as a radar system were conducted to prove the presence or absence of a barrier effect on the detection of vital signs of respiration using a radar system. The measurement results showed that the largest peak-to-peak signal amplitude decrease occurred in the target detection with a distance of 125 cm, which was 11.51 dB, and a delay of 0.084 ns when using the Hebel brick barrier. Meanwhile, in wooden barriers, the average decrease in peak-to-peak signal amplitude was 2.968 dB, and the delay was 0.006 ns.